Pengaruh Lingkungan Kerja terhadap Kinerja Karyawan Pada CV. XY - Armansyah, Armansyah; Rizki, Muhammad; Herman, Herman; Saputra, Eka Kurnia (Universitas Batanghari Jambi, 2024)
Research on the influence of the work environment on employee performance at CV. XY is an important step in understanding the factors that influence productivity and work quality in the company. In this research, a simple linear regression statistical analysis method is used to examine the relationship between the work environment and employee performance. The research results show that there is a positive (unidirectional) relationship between the work environment and employee performance at CV. XY. In other words, the better the work environment in the company, the higher the level of employee performance. These findings provide important insights for company management to improve and optimize the work environment to improve employee performance. Apart from that, this research also provides a basis for developing more effective human resource management policies and strategies at CV. XY.